The Role of Government Auditing for Combating Corruption and Promoting Integrity in Nepal - Bhul, Baburam (Khwopa Journal, 2023)
The purpose of this article is to analyze the role of government auditing for corruption control and promoting integrity in the public administration of Nepal. This article utilizes content analysis that relies on a systematic literature review of secondary sources from relevant various sources, employing content analysis as the main research strategy. In terms of corruption control, Nepal’s government auditing has been playing a crucial role in both preventive and promotional efforts, as well as corrective arrangements. Nevertheless, preventive actions are not always executed. The conclusions show that the government auditing has a major impact on fighting against corruption through Office of the Auditor General Nepal. This study also discovered that the amount of corruption and government performance had a substantial impact on governance. However, this article suggests that the competence of the auditor should be improved for making more responsible in identifying fraud and exposing corruption activities. Thus, if auditing is to play a more prominent role in the fight against corruption, auditing standards shall include specific requirements relating to control corruption, government auditors must co-operate and exchange information with other investigating agencies, auditing techniques should be made more robust to detect corruption, and the auditing profession must embrace effective preventive measures such as anticorruption recognitions and certifications. The article’s findings strongly support the promotion of good governance and the utilization of government auditing and its recommendations to enhance transparency and accountability in Nepal’s governance, benefiting political parties, governments, civic organizations, and other stakeholders.